This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Your link to the "three ways" redirects to the mobile site
Btw, great solution!
A solution that uses Newton's sums:
For easy typing purposes, let α = a , β = b , γ = c
From Vieta's formula, we get
a + b + c = 7 a b + a c + b c = 5 a b c = − 2
A = cyc ∑ b c + 1 a 3 = cyc ∑ a b c + a a 4 = cyc ∑ a − 2 a 4 = a − 2 a 4 + b − 2 b 4 + c − 2 c 4 = ( a − 2 ) ( b − 2 ) ( c − 2 ) a 4 ( b − 2 ) ( c − 2 ) + b 4 ( a − 2 ) ( c − 2 ) + c 4 ( a − 2 ) ( b − 2 ) = a b c − 2 ( a b + a c + b c ) + 4 ( a + b + c ) − 8 a 4 ( b c − 2 ( b + c ) + 4 ) + b 4 ( a c − 2 ( a + c ) + 4 ) + c 4 ( a b − 2 ( a + b ) + 4 ) = − 2 − 2 ( 5 ) + 4 ( 7 ) − 8 a 4 ( a − 2 − 2 ( 7 − a ) + 4 ) + b 4 ( b − 2 − 2 ( 7 − b ) + 4 ) + c 4 ( c − 2 − 2 ( 7 − c ) + 4 ) = − 2 − 1 0 + 2 8 − 8 a 4 ( a − 2 − 1 0 + 2 a ) + b 4 ( b − 2 − 1 0 + 2 b ) + c 4 ( c − 2 − 1 0 + 2 c ) = 8 − 2 a 3 − 1 0 a 4 + 2 a 5 − 2 b 3 − 1 0 b 4 + 2 b 5 − 2 c 3 − 1 0 c 4 + 2 c 5 = 8 2 ( a 5 + b 5 + c 5 ) − 1 0 ( a 4 + b 4 + c 4 ) − 2 ( a 3 + b 3 + c 3 )
Now, we apply Newton's sums:
a + b + c = 7 a 2 + b 2 + c 2 = ( a + b + c ) 2 − 2 ( a b + a c + b c ) = ( 7 ) 2 − 2 ( 5 ) = 3 9 a 3 + b 3 + c 3 = ( a + b + c ) ( a 2 + b 2 + c 2 ) − ( a b + a c + b c ) ( a + b + c ) + 3 ( a b c ) = ( 7 ) ( 3 9 ) − ( 5 ) ( 7 ) + 3 ( − 2 ) = 2 3 2 a 4 + b 4 + c 4 = ( a + b + c ) ( a 3 + b 3 + c 3 ) − ( a b + a c + b c ) ( a 2 + b 2 + c 2 ) + a b c ( a + b + c ) = ( 7 ) ( 2 3 2 ) − ( 5 ) ( 3 9 ) + ( − 2 ) ( 7 ) = 1 4 1 5 a 5 + b 5 + c 5 = ( a + b + c ) ( a 4 + b 4 + c 4 ) − ( a b + a c + b c ) ( a 3 + b 3 + c 3 ) + a b c ( a 2 + b 2 + c 2 ) = ( 7 ) ( 1 4 1 5 ) − ( 5 ) ( 2 3 2 ) + ( − 2 ) ( 3 9 ) = 8 6 6 7
Substitute these values in:
A = 8 2 ( a 5 + b 5 + c 5 ) − 1 0 ( a 4 + b 4 + c 4 ) − 2 ( a 3 + b 3 + c 3 ) = 8 2 ( 8 6 6 7 ) − 1 0 ( 1 4 1 5 ) − 2 ( 2 3 2 ) = 8 1 7 3 3 4 − 1 4 1 5 0 − 4 6 4 = 8 2 7 2 0 = 3 4 0
Nice... (+1)... I knew you would definitely post a solution... :-) PS:- I couldn't scroll your( and many of the solutions) on my mobile after these changes on brilliant.... Maybe you can use \ [ ...\ ] for each line next time for proper rendering... :-)
Log in to reply
Thanks. When I saw the question, I knew it was solution-writing time XD
Now that you mention it, I also can't see the last few digits for a 5 + b 5 + c 5 on my pc...lemme edit it
you don't like colors, do you? I say it because I have a doubt about your solution: weren't there more colors for using in latex?... :-----------------------------------------), Ohhhh, you didn't use yellow, what a horrible solution, you have to fix it...
Log in to reply
Yellow is too bright...
Log in to reply
I think for this exactly reason you should add it... if you don't do it, your solution will be too dark...
Log in to reply
@Guillermo Templado – I refuse :P
Log in to reply
@Hung Woei Neoh – haha, good, I was joking... Colorful solution, I have not read it but (+1)...
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Vieta's Formula Problem Solving - Intermediate
Using Vieta's formula: cyc ∑ α = 7 , cyc ∑ α β = 5 , α β γ = − 2
A = cyc ∑ ⎝ ⎜ ⎜ ⎛ − 2 α β γ + α α 4 ⎠ ⎟ ⎟ ⎞
= cyc ∑ ⎝ ⎜ ⎜ ⎜ ⎛ α − 2 α 4 1 6 + ( α 4 − 1 6 ) ⎠ ⎟ ⎟ ⎟ ⎞
= cyc ∑ ⎝ ⎜ ⎜ ⎜ ⎛ α − 2 1 6 + α − 2 ( α − 2 ) ( α + 2 ) ( α 2 + 4 ) α 4 − 1 6 ⎠ ⎟ ⎟ ⎟ ⎞
Now cyc ∑ α − 2 1 can be calculated using three ways which finally comes out to be 8 − 1 1 . Now let's calculate second expression i.e = = = = cyc ∑ ( α 2 + 4 ) ( α + 2 ) cyc ∑ α 3 + 2 α 2 + 4 α + 8 cyc ∑ ( 9 α 2 − α + 6 ) ∵ α 3 − 7 α 2 + 5 α + 2 = 0 9 ( 4 9 − 1 0 ) = 3 5 1 9 ⎝ ⎛ ( cyc ∑ α ) 2 − 2 cyc ∑ α β ⎠ ⎞ − 7 + 6 × 3 3 6 2
Hence,
A = 1 6 ( 8 − 1 1 ) + 3 6 2 = 3 4 0